Reading Strategies for Non-English Department Students: How Important is It? - Zusana E. Pudyastuti (Prosodi Jurnal Ilmu Bahasa dan Sastra, 2019)
Lack of English knowledge, lack of vocabulary and incapability in using reading strategies might become the reasons of most higher education students, particularly the students of non-English department, to feel reluctance reading in L2. For becoming successful and strategic readers, reading strategies are crucial. Unfortunately, the non-English department students are not taught about reading strategies which hinders their reading comprehension. A survey had been conducted to know more on the students’ attitude towards reading strategies for comprehending reading materials. The subject of this study was 28 students of non-English department students in a college in Malang. The study found out that most of the students considered that using reading strategies in their reading process was not necessary even though they had shown a positive attitude towards the use of reading strategies. Moreover, the implementation of reading strategies had not been able to improve their motivation in reading a text in English because most of them were not fully motivated. Thus, it can be concluded that reading strategies should be taught explicitly to the students of non-English department for improving their reading comprehension and for developing a good reading habit.